HIV intertest interval among MSM in King County, Washington. Issue 1 (5th May 2012) - Katz, David A; Dombrowski, Julia C; Swanson, Fred; Buskin, Susan E; Golden, Matthew R; Stekler, Joanne D
Abstract : Objectives: The authors examined temporal trends and correlates of HIV testing frequency among men who have sex with men (MSM) in King County, Washington. Methods: The authors evaluated data from MSM testing for HIV at the Public Health—Seattle & King County (PHSKC) STD Clinic and Gay City Health Project (GCHP) and testing history data from MSM in PHSKC HIV surveillance. The intertest interval (ITI) was defined as the number of days between the last negative HIV test and the current testing visit or first positive test. Correlates of the log10 -transformed ITI were determined using generalised estimating equations linear regression. Results: Between 2003 and 2010, the median ITI among MSM seeking HIV testing at the STD Clinic and GCHP were 215 (IQR: 124–409) and 257 (IQR: 148–503) days, respectively. In multivariate analyses, younger age, having only male partners and reporting ≥10 male sex partners in the last year were associated with shorter ITIs at both testing sites (p<0.05). Among GCHP attendees, having a regular healthcare provider, seeking a test as part of a regular schedule and inhaled nitrite use in the last year were also associated with shorter ITIs (p<0.001). Compared with MSM testing HIV negative, MSM newly diagnosed with HIV had longer ITIs at the STD Clinic (median of 278 vs 213 days, p=0.01) and GCHP (median 359 vs 255 days, p=0.02). Conclusions: Although MSM in King County appear to be testing at frequent intervals, further efforts are needed to reduce the time that HIV-infected persons are unaware of their status.